2016
DOI: 10.1080/17470218.2015.1085586
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval-induced forgetting is associated with increased positivity when imagining the future

Abstract: People often think of themselves and their experiences in a more positive light than is objectively justified. Inhibitory control processes may promote this positivity bias by modulating the accessibility of negative thoughts and episodes from the past, which then limits their influence in the construction of imagined future events. We tested this hypothesis by investigating the correlation between retrieval-induced forgetting and the extent to which individuals imagine positive and negative episodic future ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Giebl, Storm, Buchli, Bjork, and Bjork (2016) measured positivity bias using a similar procedure to Storm and Jobe (2012), in which the number of positive future events that could be constructed in response to 20 neutral cue words was compared to the number of negative events that could be constructed in response to a second set of 20 cue words. Using this method, a significant correlation was found only between RIF and negative future episodic thinking, whereas correlations between RIF and positive future thinking did not reach significance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Giebl, Storm, Buchli, Bjork, and Bjork (2016) measured positivity bias using a similar procedure to Storm and Jobe (2012), in which the number of positive future events that could be constructed in response to 20 neutral cue words was compared to the number of negative events that could be constructed in response to a second set of 20 cue words. Using this method, a significant correlation was found only between RIF and negative future episodic thinking, whereas correlations between RIF and positive future thinking did not reach significance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by Storm and Jobe (2012) and Giebl et al (2016) found relationships between positivity biases and RIF based on the number of positively valenced past or future episodes relative to the number of negative episodes that participants could generate. Participants were thereby constrained in their retrieval search by the valence category (positive or negative).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, the findings indicate that spontaneous memory retrieval, which underlies the intention superiority effect, supports episodic future simulation. While there are some studies on the retrieval process for episodic future simulation (Szpunar, 2010; Storm and Jobe, 2012; Giebl et al, 2015; Ditta and Storm, 2016), this is the first to explore the role of spontaneous memory processing in such simulation. This form of processing naturally depends on the mechanism of prospective memory, causing context-sensitive intention superiority effect.…”
Section: Discussionmentioning
confidence: 99%
“…Ditta and Storm (2016) test the assumption that memory and future thinking are closely related to one another by assessing the extent to which the generation of future events may actually reduce the accessibility of related autobiographical experiences in memory. Giebl, Storm, Buchli, Bjork, and Bjork (2016) extend this viewpoint by assessing correlations between an index of retrieval induced forgetting and the propensity for individuals to generate positive as opposed to negative future events. While the results of this latter study raise interesting insights into the positivity biases that commonly characterize memory (Walker & Skowronski, 2009) and future thinking (Szpunar et al, 2012), the reported data also call for more work to establish causal links between measures of retrieval-induced forgetting and positivity in event cognition.…”
Section: Contents Of This Issuementioning
confidence: 99%